BREAST CANCER TYPING USING RT-PCR ASSAY - V. K. Bozhenko (Sibirskij Onkologičeskij Žurnal, 2019)
Introduction. Adjuvant systemic therapy remains one of the main options for treating breast cancer. Results of standard immunohistochemical studies are not always a criterion for selecting systemic therapy. Nowadays, multigene expression analysis is actively used to predict the response to chemotherapy in patients with earlystage breast cancer. We studied a 24-gene multi-gene panel for typing breast cancer.Material and Methods. A prospective analysis of 199 breast cancer patients (T1–3N0–3M0) was carried out. Surgical specimens were studied using the standard immunohistochemistry (IHC) and RT-PCR for detecting expression of 24 genes.Results. According to the IHC results, breast cancer was divided into 5 molecular subtypes: luminal A was detected in 59 (30 %) patients; luminal B (HER2-negative) in 52 (26 %); luminal B (HER2-positive) in 19 (9 %); triple-negative in 28 (14 %); HER2-positive 41 (21 %). RT-PCR showed that ST K15, MYC, MYBL2, BIRCC 5, BCL2, TERT, ESRP1, PGR, HER2, GBR7, MGB1 and MMP11 were the most significant genes in subtype distribution. The total percentage of matches between the two studies was 61.7 %.Conclusion. Studies have shown the need to add additional typing methods for breast cancer to a standard IHC study, which will undoubtedly increase the information content of diagnostic measures and will improve the effectiveness of the treatment.